PENGARUH BUDAYA ORGANISASI TERHADAP MOTIVASI DAN KEPUASAN KERJA SERTA KINERJA KARYAWAN BANK BJB CABANG SURABAYA - jurnalpps pps; Andika Budi Ratwono; Indra Prasetyo; Subijanto ÔÇÄ (Jurnal Manajerial Bisnis, 2019)
The purpose of this study to determine the influence of organizational culture and motivation. Job satisfaction and employee performance. Variables used in this research are organizational culture, motivation as independent variable, employee performance as dependent variables, job satisfaction as intervening variable. The analytical unit is an employee of Bank BJB Surabaya branch in Surabaya. The population in this study amounted to 115 employees with a sample of 100 respondents. Technical analysis used is SEM (Structure Equation Model) analysis. The result of the research is organizational culture have positive effect to the motivation, organizational culture have positive effect to job satisfaction, motivation are positive influence to job satisfaction, organizational culture have positive influence to performance, motivation have positive influence to performance, job satisfaction have a positive effect on performance.